Encyclia, Epidendrum, or Prosthechea? Clarifying the Phylogenetic Position of a Rare Amazonian Orchid (Laeliinae-Epidendroideae-Orchidaceae) - Klein, Viviane Pagnussat; Pessoa, Edlley Max; Demarchi, Layon Oreste; Sader, Mariela A.; Piedade, Maria Teresa Fernandez (Systematic Botany, 2019)
The phylogenetic position of a rare orchid species, which was described by Mansfeld from the Brazilian Amazon, is discussed. Although originally described under Epidendrum despite having a column that is not fully adnate to the lip claw, a feature not common in this genus, Epidendrum apuahuense has been transferred to Encyclia and Prosthechea by other authors. About 90 yr after its description, we found a new population of this species in Brazil, which allowed us to study its taxonomy. A phylogenetic reconstruction was performed using nuclear (ITS rDNA) and plastid (matK exon, rpl32-trnL spacer, trnL intron, and trnL-trnF spacer) datasets, aiming to clarify the generic placement of this taxon. Our results strongly support keeping E. apuahuense under Epidendrum. We also neotypify this name, since the original specimens were destroyed and no illustration is available. The morphological affinities of E. apuahuense and allied taxa are discussed. © 2019 by the American Society of Plant Taxonomists.